2007
DOI: 10.1016/j.jcrs.2006.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 360-degree enhanced optic edge design of a hydrophilic acrylic intraocular lens on posterior capsule opacification

Abstract: The C-flex IOLs showed good functional results and significantly lower PCO formation than the earlier model Centerflex IOL. The enhanced edge of the C-flex IOL seemed to improve PCO prevention clinically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 29 publications
3
27
0
1
Order By: Relevance
“…It is well documented that IOL edge design is an important factor in the pathogenesis of PCO and that a square-edged optic (as in the IOL we used) results in a lower PCO rate than a round-edged optic. 18,19, In conclusion, based on our evaluation of postoperative visual outcomes, we conclude that the M-flex 630F C3 refractive multifocal IOL is an effective alternative to monofocal IOLs and provides excellent distance and intermediate vision, sufficient functional near vision, good contrast sensitivity, and a low incidence of visual disturbances and PCO remain. We recommend studies of whether a model with a C4.00 D add would improve the near-vision performance of this IOL.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…It is well documented that IOL edge design is an important factor in the pathogenesis of PCO and that a square-edged optic (as in the IOL we used) results in a lower PCO rate than a round-edged optic. 18,19, In conclusion, based on our evaluation of postoperative visual outcomes, we conclude that the M-flex 630F C3 refractive multifocal IOL is an effective alternative to monofocal IOLs and provides excellent distance and intermediate vision, sufficient functional near vision, good contrast sensitivity, and a low incidence of visual disturbances and PCO remain. We recommend studies of whether a model with a C4.00 D add would improve the near-vision performance of this IOL.…”
Section: Discussionmentioning
confidence: 66%
“…The IOL has a 360-degree square edge to prevent lens epithelial cell migration and thus posterior capsule opacification (PCO). 18,19 The IOL material is a proprietary hydrophilic acrylic copolymer with an ultraviolet (UV) light filter. The water content is 26% and the refractive index, 1.46.…”
Section: Intraocular Lensmentioning
confidence: 99%
“…Rabbit and clinical studies found a better barrier effect against lens epithelial cell (LEC) migration with this design than with the earlier version (model 570H) with a smooth optic-haptic transition. 6,[21][22][23] The study IOL evaluated in our study has loops that are thinner close to the optic-haptic junctions, creating beveled barrier steps anteriorly and posteriorly to enhance prevention of cell migration/proliferation toward the visual axis. Even though PCO started at the level of the optic-haptic junctions in 3 of 5 eyes with the study IOL (versus 4 of 5 control eyes), significantly less PCO was observed in the study eyes at the end of the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…It is manufactured from the same material used in the C-flex IOL (Rayner Intraocular Lenses Ltd.), which was approved for sale by the U.S. Food and Drug Administration for in-the-bag implantation. [18][19][20] One problem reported with initial piggyback implantation of IOLs is the formation of ILO. 8,9 Several methods to prevent ILO, including creation of a relatively large capsulorhexis and implantation of the piggyback IOL in the ciliary sulcus rather than in the capsular bag, have been shown to decrease the incidence of this complication.…”
Section: Discussionmentioning
confidence: 99%
“…14 The uveal biocompatibility of its hydrophilic acrylic material has been described in clinical studies of other IOL designs (eg, Rayner C-flex). [18][19][20] The optic has round and smooth edges, and the undulating, relatively thin haptics also have a smooth surface with round edges, all of which may account for minimal uveal tissue interaction. Also, the posterior optic-haptic angulation is said to provide appropriate uveal clearance.…”
Section: Discussionmentioning
confidence: 99%